Routine clinical application of virtual reality in abdominal surgery. Issue 3 (4th May 2017) - Sampogna, Gianluca; Pugliese, Raffaele; Elli, Marco; Vanzulli, Angelo; Forgione, Antonello
Abstract: Background: The advantages of 3D reconstruction, immersive virtual reality (VR) and 3D printing in abdominal surgery have been enunciated for many years, but still today their application in routine clinical practice is almost nil. We investigate their feasibility, user appreciation and clinical impact. Material and methods: Fifteen patients undergoing pancreatic, hepatic or renal surgery were studied realizing a 3D reconstruction of target anatomy. Then, an immersive VR environment was developed to import 3D models, and some details of the 3D scene were printed. All the phases of our workflow employed open-source software and low-cost hardware, easily implementable by other surgical services. A qualitative evaluation of the three approaches was performed by 20 surgeons, who filled in a specific questionnaire regarding a clinical case for each organ considered. Results: Preoperative surgical planning and intraoperative guidance was feasible for all patients included in the study. The vast majority of surgeons interviewed scored their quality and usefulness as very good. Conclusions: Despite extra time, costs and efforts necessary to implement these systems, the benefits shown by the analysis of questionnaires recommend to invest more resources to train physicians to adopt these technologies routinely, even if further and larger studies are still mandatory.